Smart car navigation system based on A.R.M technology / Mohamad Syariffudin Ibrahim, Mohamad Famee Jumingan and Muhammad Nur Fahmi Ali - Ibrahim, Mohamad Syariffudin; Jumingan, Mohamad Famee; Ali, Muhammad Nur Fahmi (2014)
Most of modem vehicle are using manual control system that need human to sense, control steering, clutch and throttle. Thus, human errors might cause accident especially when the car loss of control. Therefore, this project is carried out to develop a smart car model that will navigate automatically on specific path. A CMOS camera is used to detect a black lane on the custom track. The route information is sent to ARM processor and the steering angle of the car is determined. As a result, the car manage to steer automatically in various route condition such as straight line, ramp, intersection line and also sharp turn.